ABOUT THE FUNCTIONAL NATURE OF THE TURKISH IZAFET (Scientific journal of the Fergana State University, 2023)
This article analyzes the nature of the turkish izafet, izafet in the turkish languages and their types, the degree of research of the Turkish izafet by turkologists .